2017
DOI: 10.18203/2320-1770.ijrcog20171421
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological analysis of cervical polyps

Abstract: Background: Cervical polyps are the commonest cervical lesions and occur in about 2-5% of women. It is common practice to remove these polyps whenever they are identified and the main reason for this is the concern over the potential for malignant transformation. This study was done to analyse the spectrum of histopathological diagnosis in cases of cervical polyps and to identify focus of malignancy if present. This would help us to improve further management of cases of symptomatic and asymptomatic cervical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
2
2
0
Order By: Relevance
“…18,8 Gopalan et al, Tirlapur, Senturk et al and Mackenzie et al also found no features of atypia, dysplasia or malignancy. 1,14,19,20 Mackenzie at al also questioned the removal of polyp unless symptomatic, similar to this study asymptomatic cases also came up in our study. 20…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…18,8 Gopalan et al, Tirlapur, Senturk et al and Mackenzie et al also found no features of atypia, dysplasia or malignancy. 1,14,19,20 Mackenzie at al also questioned the removal of polyp unless symptomatic, similar to this study asymptomatic cases also came up in our study. 20…”
Section: Discussionsupporting
confidence: 87%
“…A study by Gopalan et al reported endocervical mucous polyp to be the most common lesion (50.5%) followed by benign endometrial polyp (21.5%) and leiomyomatous polyp in 13.1%. 1 Another study by Nelson et al also found endocervical polyp (57.1%) to be the most common followed by inflamed endocervical polyp (21%). Both the studies had finding concordant to findings in our study.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Saravanan et al, 2015, documented only about six percent of cases in their study of cervical lesions [46]. These fibroepithelial proliferations were observed to occur most commonly in the 4 th and 5 th decades of life as had been described earlier [47,48,49,50]. The current study has shown that inflammatory squamous (ec-tocervical) polyps were the most abundant variety in contrast to that described by Sidhalingreddy et al, 2013, where most polyps were endocervical in origin [51].…”
Section: Discussionsupporting
confidence: 63%